Combining strategies to make General Physics lectures more attractive and to improve students' performances. (August 2019) - López, G A; Alonso, I; Sáenz, J; Leonardo, A; González-Rojí, S J; González de Arrieta, I; Echániz, T; Unzueta, I; Lafuente-Bartolome, J; de la Pinta, N; García-Goiricelaya, P; Martinez-Perdiguero, J; et al.
Abstract: Going one step further in the use and impact measurement of new strategies to improve the teaching-learning process during lecturing General Physics courses, the current contribution reports the last results/observations obtained by the authors on the combination of simple classroom experiments with active methodologies and new technologies (media). Cross-checking the answers in multiple choice questions done online during the lectures and in exams at the end of the term shows that this strategy has, at least partly, a positive effect on clarifying misconceptions. The overall opinion of the students was assessed and it showed that this lecturing approach is useful and motivating, making the lectures more attractive and stimulating eagerness to understand Physics.